The cognitive neuroscience of bilingualism - Schwieter, John W. 1979-; Festman, Julia (Cambridge fundamentals of neuroscience in psychology, 2023)
The Cognitive Neuroscience of Bilingualism presents an introduction to the neural bases and cognitive processes of the bilingual brain. It covers foundational knowledge required for study in the area of bilingualism, including prominent theories and research methodologies, and the state of research in relevant fields of psycholinguistics, cognitive psychology, and neuroscience. Major topics include bilingual development and brain plasticity; aphasia and the bilingual brain; cross-linguistic effects of bilingualism; bilingual lexical and conceptual memory; and cognitive and neurocognitive effects of bilingualism. This book represents the first of its kind to bring together the various psychological and theoretical issues of bilingualism with respect to language processing and representation, while providing insight into the 'reality' of the bilingual brain